(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Augmented Reality (AR) and Virtual Reality (VR) have revolutionized the gaming industry, delivering immersive experiences that transcend traditional gaming boundaries in recent years, AR and VR technologies have gained attention great, changing the way users interact with games. AR overlays digital objects into the real world, while VR is a fully immersive simulated environment. The fusion of this technology has changed gaming, providing players with unparalleled engagement, interactivity, and virtual reality. One of the most important impacts of AR and VR in gaming is to enhance the user experience. AR enables players to integrate digital objects with their physical surroundings, allowing them to blend virtual and virtual interactions. This integration enables a unique gaming experience, creating new dimensions of immersion and interactivity. On the other hand, V.R. This technology allows gamers to engage with their favourite titles in ways previously unimaginable. Additionally, AR and VR have increased the innovation of games in the gaming industry. Developers now have the opportunity to explore new ideas and gaming technologies, and the market has expanded with the introduction of AR-enabled mobile games and high-end VR headsets to leverage these technologies to create a variety of experiences it challenges traditional game values. possibilities on offer. Despite these advances, there are still challenges to the widespread use of AR and VR in gaming. Technical constraints such as hardware requirements and cost may hinder some users. Additionally, creating content that maximize the potential of AR and VR demands specialized skill and resource, posting a barrier for smaller game development team.